Navigating complexity: adaptive management and organizational learning in a development project in Northern Uganda - Allana, Amir; Sparkman, Timothy (Knowledge Management for Development Journal, 2014)
Adaptive management is a management paradigm for intervening in complex, unpredictable systems where continual learning and adaptation is vital for success. This management approach requires a fundamentally different set of tools, processes, and most importantly, staff behaviors and organizational culture than ‘traditional’ management. A facilitative approach to development, where the goal is creating systemic change that spreads in networks of local businesses, government, and civil society organizations, necessitates an adaptive approach. Mercy Corps Uganda’s Northern Karamoja Growth, Health, and Governance Program (GHG) has been an ongoing experiment in applying the principles of adaptive management and facilitation. This article details two examples from GHG where adaptation has occurred, and provides an analysis of the tools, processes, and organizational culture that exists. Three salient takeaways for effective facilitation are elaborated on: the importance of staff behaviors and underlying beliefs, particularly with regards to ‘failure’, flexibility to experiment, dissent & debate, and curiosity with the subject matter of their work; importance of consistent messaging from senior management with regards to the same; and tools and processes playing a support function to these behaviours, rather than being their source. Lessons and implications are drawn out from the GHG experience for funders and implementing organizations wanting to apply adaptive management in the context of development programming. These include building flexibility into budgeting and contracts, rethinking the structure and content of reports, and utilizing alternative hiring criteria to attract senior managers who are more likely to succeed at adaptive management.

Learning and adapting: the use of monitoring and evaluation in countering violent extremism: a handbook for practitioners - Dawson, Laura; Edwards, Charlie; Jeffray, Calum; Royal United Services Institute for Defence and Security Studies (Royal United Services Institute for Defence and Security Studies, 2014)
IN 2013, the Royal United Services Institute for Defence and Security Studies (RUSI) was awarded a grant under the Kanishka Project to develop a handbook for monitoring and evaluating counter violent extremism (CVE) policies and programmes. The aim of this handbook is to support CVE policy-makers and practitioners (those who design, manage and evaluate CVE programmes), by providing them with key terms regarding violent extremism and radicalisation, describing the purpose of evaluation, and providing examples of key methodologies they can employ to conduct monitoring and evaluation (M&E) in this emerging policy field. The handbook will enable readers to understand why, when and how to conduct an evaluation of a CVE policy, programme or project. .
OCLC: 1079851950

The SAVI programme in Nigeria: Towards politically smart, locally led devlopment - Booth, David; Chambers, Victoria (ODI, 2014)
 More examples are needed of aid programming that works by being responsive to country realities: politically smart, problem-driven and locally led  DFID’s SAVI programme has revealed a hitherto untapped potential for change leading to better development results at state level in Nigeria  SAVI provides low-profile support to state-level organisations and partnerships, building their capacity to engage constructively with government  It avoid the pitfalls of a donor-driven approach by ‘taking the money off the table’  This illustrates the power of facilitated multi-stakeholder engagement and the disadvantages of seeing this in terms of ‘supply side’ and ‘demand side’ governance  The set-up of the DFID suite of state-level programmes, with separately managed sector support and ‘governance’ initiatives, has limited realisation of the potential  Key enabling conditions were that DFID provided space for an experience-based design process and permitted tangible results to be judged retrospectively, not pre-programmed

Emerging Technologies: Smarter ways to fight wildlife crime - Cressa, Douglas; Zommers, Zinta (Environmental Development, 2014)
The illegal trade of animals—for luxury goods, traditional medicine or cultural ceremonies, pets, entertainment, and even research—is a major threat to wildlife conservation and welfare (Baker et al., 2013). Poachers and illegal traders use highly sophisticated and rapidly changing techniques to avoid detection. To keep pace with the "war on wildlife", conservation and law enforcement communities have started to adopt cutting-edge military tools and techniques. High-tech equipment can magnify counter-poaching efforts without requiring armies of rangers or risking lives. Tools include acoustic traps, mobile technology, mikrokopters, radio frequency identification tags, encrypted data digital networks, camera traps, DNA testing, radio collars, metal scanners, and satellite imagery.

Behavioral Design: A New Approach to Development Policy - Datta, Saugato; Mullainathan, Sendhil (Review of Income and Wealth, 2014)

Evaluating Complexity. Propositions for improving practice - Preskill, Hallie; Gopal, Srik (FSG, 2014)
9 propositions can help evaluators measure progress on complex social problems.
Keywords: IMPORTANT

Local Systems: a framework for supporting sustained development - USAID (USAID, 2014)

From best practice to best fit: understanding and navigating wicked problems in international development - Ramalingam, Ben; Laric, Miguel; Primrose, John (ODI, 2014)